Human V-ATPase a2 P405L Mutation Results in Cutis Laxa by Affecting V-ATPase Assembly and/or Stability - Kumar, Ravi; Bhargava, A.; Manolson, M. (The Meducator, 2012)
Cutis Laxa is a genetic disorder in which a patient’s skin becomes loose and inelastic. The autosomal recessive variant of this disorder has been linked to a genetic mutation in vacuolar-type H+-ATPase (V-ATPase). This enzyme contains a cytosolic domain, responsible for hydrolyzing ATP, and a membrane-bound domain that actively transports protons across intracellular and plasma membranes. Proton pumping regulates housekeeping functions inside the cell, resorption of bone, and acidification of urine. A human missense mutation in one of the V-ATPase subunits (a2 P405L) that causes Cutis Laxa was recreated in the yeast V-ATPase to elucidate why a single amino acid change could affect enzyme activity. The mutation recreated in the yeast V-ATPase disrupted activity based on the inability of yeast to acidify their vacuoles. The membrane domain of the mutant V-ATPase was correctly assembled and targeted to the yeast vacuole but the cytosolic domain was not attached explaining why the vacuoles were not acidic. These results suggest that the loss-of-function mutation present in cutis laxa leads to decreased V-ATPase stability and/or assembly. Further experiments will be designed to assess if the mutation results in a conformational defect, and if so, therapeutics assisting in protein folding can be explored. Such therapeutics not only hold promise for cutis laxa, but also for other V-ATPase genetic diseases such as osteopetrosis, distal renal tubular acidosis and male sterility.